An inter-organisational perspective on challenges in one-stop government. (29th September 2008) - Axelsson, Karin; Melin, Ulf
Fragmentation and isolated development are main problems that hinder successful e-government. This paper has an inter-organisational perspective on challenges in one-stop government. We present a conceptual framework that characterises an inter-organisational relationship and its dimensions. The conceptual framework is used for analysing data from an inter-organisational one-stop government project. When applying the framework we focus on some interesting issues and explain some of the challenges that our interviewees identified. By addressing these inter-organisational aspects we reached further understanding of the problems associated with this case, which can provide added value to discussions of e-government challenges, barriers and problems in general.